RANCANGAN DASAR GASIFIER BATUBARA SIRKULASI UNGGUN MENGAMBANG UNTUK MEMBANGKITKAN LISTRIK 1 MW - Tirtosoekotjo, Soedjoko; Rahardjo, Bambang Suwondo (Jurnal Energi dan Lingkungan (Enerlink), 2011)
There are 3 choices in accommodating power station facility which have beeninstalled to fulfill standard regulation of environmental quality which progressivelytighten. Firstly, facility modification of pulverized?coal fired power plant byapplying a flue?gas desulfurisation technology throw away to cost moneyinstallation of tired which can 20% of total cost development of it. Secondly,modification system of coal fired power generation become natural gas combinedcycle (NGCC) can reach low emission, but fuel cost relatively high, so willinfluence the electricity generating cost. Third, modification system of electricgeneration which have been installed by utilizing a mechanism of coalgasification is most efficient and best alternative to yield an environmentalfriendly of electric generation combined cycle. In this paper, writer try to make abasic design of circulating fluidized?bed coal gasifier using clay catalist relatedon third choice which expected applicable in the next future to come replacepower station system which have ended a period as well as newly even if.Kata Kunci: gasifier batubara unggun mengambang, katalis tanah liat,pembangkit listrik